An innovative housing-related measure for individual socioeconomic status and human papillomavirus vaccination coverage: A population-based cross-sectional study. Issue 39 (3rd September 2020) - MacLaughlin, Kathy L.; Jacobson, Robert M.; Sauver, Jennifer L. St.; Jacobson, Debra J.; Fan, Chun; Wi, Chung-Il; Finney Rutten, Lila J.
Highlights: Prior study results are inconsistent for association between socioeconomic status (SES) and HPV vaccination. A novel, individual-level housing-based SES marker was used for this study. Increased rates of HPV vaccine coverage were observed with higher housing-based SES levels. The moderating effect of higher SES on HPV vaccination differed by age, sex, and race. Abstract: Background: Human papillomavirus (HPV) is a known cause of anogenital (eg, cervical) and oropharyngeal cancers. Despite availability of effective HPV vaccines, US vaccination-completion rates remain low. Evidence is conflicting regarding the association of socioeconomic status (SES) and HPV vaccination rates. We assessed the association between SES, defined by an individual validated Housing-based Index of Socioeconomic Status (HOUSES), and HPV vaccination status. Methods: We conducted a cross-sectional study of children/adolescents 9–17 years as of December 31, 2016, living in southeastern Minnesota by using a health-record linkage system to identify study-eligible children/adolescents, vaccination dates, and home addresses matched to HOUSES data. We analyzed the relationship between HPV vaccination status and HOUSES using multivariable Poisson regression models stratifying by age, sex, race, ethnicity, and county. Results: Of 20, 087 study-eligible children/adolescents, 19, 363 (96.4%) were geocoded and HOUSES measures determined. In this cohort, 57.9% did not receive HPV vaccination, 15.8% initiated (only), and 26.3% completed the series. HPV vaccination-initiation and completion rates increased over higher SES HOUSES quartiles ( P  < .001). Rates of HPV vaccination initiation versus unvaccinated increased across HOUSES quartiles in multivariable analysis adjusted for age, sex, race, ethnicity, and county (1st quartile, referent; 2nd quartile, 0.97 [0.87–1.09]; 3rd quartile, 1.05 [0.94–1.17]; 4th quartile, 1.15 [1.03–1.28]; test for trend, P  = .002). HOUSES was a stronger predictor of HPV vaccination completion versus unvaccinated (1st quartile referent; 2nd quartile, 1.06 [0.96–1.16]; 3rd quartile, 1.12 [1.03–1.23]; 4th quartile, 1.32 [1.21–1.44]; test for trend, P  < .001). Significant interactions were shown for HPV vaccination initiation by HOUSES for sex ( P  = .009) and age ( P  = .006). Conclusion: The study showed disparities in HPV vaccination by SES, with the highest HOUSES quartiles associated with increased rates of initiating and even greater likelihood of completing the series. HOUSES data may be used to target and tailor HPV vaccination interventions to undervaccinated populations.